Serious Cardiovascular Adverse Events Reported with Intravenous Sedatives: A Retrospective Analysis of the MedWatch Adverse Event Reporting System - Duprey, Matthew S. (Drugs Real World Outcomes, 2019)
BACKGROUND: Serious cardiovascular adverse events (SCAEs) associated with intravenous sedatives remain poorly characterized. OBJECTIVE: The objective of this study was to compare SCAE incidence, types, and mortality between intravenous benzodiazepines (i.e., diazepam, lorazepam, and midazolam), dexmedetomidine, and propofol in the USA over 8 years regardless of the clinical setting where it was administered. METHODS: The Food and Drug Administration’s MedWatch Adverse Event Reporting System was searched between 2004 and 2011 using the Evidex(®) platform from Advera Health Analytics, Inc. to identify all reports that included one or more of ten different SCAEs (package insert incidence ≥ 1%) and where an intravenous benzodiazepine, dexmedetomidine, or propofol was the primary suspected drug. RESULTS: Among the 2326 Food and Drug Administration’s MedWatch Adverse Event Reporting System cases reported, 394 (16.9%) were related to a SCAE. The presence of a SCAE (vs. a non-SCAE) is associated with higher mortality (34 vs. 8%, p < 0.001). The percentage of cases with one or more SCAE, the case mortality rate (%), and the incidence of each SCAE (per 10(6) days of sedative exposure), respectively, were benzodiazepines (14, 26, 13) [diazepam (13, 23, 31); lorazepam (15, 43, 14); midazolam (14, 20, 11)]; dexmedetomidine (40, 15, 13); and propofol (17, 39, 7). Propofol (vs. either a benzodiazepine or dexmedetomidine) was associated with more total SCAEs (268 vs. 126, p < 0.001) but a lower incidence (per 10(6) days of sedative exposure) of SCAE (7 vs. 13, p = 0.0001) and cardiac arrest [6.3 (benzodiazepine) vs. 6.7 (dexmedetomidine) vs. 1.4 (propofol), p < 0.0001]. CONCLUSIONS: Serious cardiac adverse events account for nearly one-fifth of intravenous sedative Food and Drug Administration’s MedWatch Adverse Event Reporting System reports. These SCAEs appear to be associated with greater mortality than non-cardiac serious adverse events. Serious cardiac events may be more prevalent with either benzodiazepines or dexmedetomidine than propofol. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40801-019-00161-y) contains supplementary material, which is available to authorized users.